Carbon molecular sieves from palm shell: Effect of the benzene deposition times on gas separation properties - Daud, W.M.A.W.; Ahmad, M.A.; Aroua, M.K. (Separation and Purification Technology, 2007)
In the present work, an effort has been made to develop suitable process conditions for synthesis of carbon molecular sieve (CMS) from a locally available palm shell of Tenera type. The process involves three stages; carbonization, physical activation with steam, and carbon deposition by using benzene cracking technique. The highest micropore volume of activated carbon was obtained at 53.2 burn-off, which is then used as a precursor for CMS production. In order to narrow down the pore mouth size to a required size, benzene was cracked at 800 Â°C for 15-60 min. The characterization of the samples was assessed by physical adsorption of N2 at 77 K. The adsorption kinetic of CO2, CH4, O2 and N2 were measured at room temperature in order to determine the sample behavior as CMS.